Nada sobre nós sem nós: os sentidos de vida independente para os militantes de um movimento de pessoas com deficiência - Cordeiro, Mariana Prioli (2007)
The social movements created by deficient people have had a profound effect on the quality of their lives. Such initiatives pertain to education, work, health and the involvement of these people in every social aspect of life. This work is about one of these movements, the Independent Living Movement (ILM). In this study, we aimed to identify the terms used to convey the feeling of independent living, as well as the possibilities associated with this life style. To complete this work, we acquired input from deficient people, an uncommon practice for projects of this nature. Besides allowing those people to speak, this work also aimed to fill a gap in the literature about deficiency and social movements the scarce literature regarding ILM. This movement s principles are in place in various countries and play an important role in international politics, which is why we thought these studies were important. To perform our studies, we analyzed, according to a constructionist perspective, documents from public domain produced by ILM and we conducted two focus groups with some of its members. Our findings indicated that independent life is understood as praxis, i.e., the process of putting theoretical knowledge into practice. In addition, we verified that the terms used to convey the concept of independent life were: independence, autonomy, empowerment, self-determination, participation and equal opportunities. The analysis of the documents from public domain and the focus groups allowed us realize that all these terms contributed to a new way of understanding deficiency. Using and practicing these terms, ILM members seek recognition as social actors, involvement in society and control of their lives. They believe the personal autonomy and the independent living are the factors that turn this reality possible. In other words, they believe that deficient people need to be accepted as ordinary citizens, without being stratified and be able to help each other to confront the social stigma that labels them as second-class citizens